Noise Sensitivity (Hyperacusis) Due to Covid-19: The First Report of a New Corona Symptom - Safoura Khodaei; Arash Momeni Safarabadi; Fatemeh Mehrabi Rad; Pegah Shakib; Maede Nilechi (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Coronaviruses are a large family of viruses and a subset of Coronaviridae. The present studyis the first report of voice sensitivity in patients with Covid-19.Case Report: In this case report, the patient was a 35-year-old man who referred to a private clinicspecializing in infectious and febrile diseases on October 26, 2016. According to the clinical symptoms andlaboratory test, the coronary test of the patient SARS-COV-2 (RdRp gene) and (E gene) SARS-COV-2 waspositive. The patient suffers from severe noise sensitivity from the first day of infection until 10 days aftertreatment.Conclusions: The patient was so sensitive to sound that different sounds had painful and excruciating effectson the patient’s mind and psyche. Therefore, sensitivity to sound can be one of the symptoms of Covid-19.